Zinc- and cadmium-isotope evidence for redox-driven perturbations to global micronutrient cycles during Oceanic Anoxic Event 2 (Late Cretaceous) - Sweere, TC; Dickson, AJ; Jenkyns, HC; Porcelli, D; Henderson, GM (Elsevier, 2020)
This study uses organic-rich sediments from the Tarfaya Basin, Morocco, to assess the Cd- and Zn-isotope response to dramatic global palaeoenvironmental change during the Cenomanian–Turonian interval (Late Cretaceous). These organic-rich continental-margin deposits include an expression of Oceanic Anoxic Event 2 (OAE 2, ∼94 Ma), an interval associated with the spread of low-oxygen marine environments and widespread burial of organic-rich sediments. Due to placement of the Tarfaya Basin in a region of upwelling and relatively constant local environmental conditions, the stratigraphic variations in δ114Cd and δ66Zn values largely reflect changes in the seawater isotopic composition of the sub-surface proto-North Atlantic Ocean. Positive shifts of ∼0.2–0.3‰ away from background values in δ114Cd and δ66Zn are observed during the main phase of the positive carbon-isotope excursion associated with OAE 2. These isotopic shifts are coeval with decreases in Cd/TOC and Zn/TOC ratios and thus imply that drawdown of isotopically light Cd and Zn from seawater inventories was a result of extensive burial of these metals in organic-rich marine sediments globally. Low δ66Zn values during the Plenus Cold Event, a cooler episode during OAE 2, are similar in timing and magnitude to variations found in the English Chalk (Eastbourne, UK) and support the inference of a global control on these isotopic excursions. The δ66Zn values during the Plenus Cold Event are taken to record global oxygenation, possibly including the remobilization of isotopically light Zn from continental-margin sediments. A considerably smaller change in δ114Cd values for this interval implies that the Cd- and Zn-isotope systems can provide information about slightly different environmental processes, with global seawater composition with respect to Zn also being influenced by the magnitude of oxic removal sinks and isotopically light Zn input fluxes from sediments and hydrothermal fluids.